AN ERROR ANALYSIS OF TRANSLATION FROM TETUM TO ENGLISH AT FIRST GRADE SECONDARY SCHOOL COLÉGIO PAULO VI DILI - TIMOR LESTE IN ACADEMIC YEAR 2017 - NURHAYATI, AGUSTINA (IJRDO- Journal of Educational Research, 2017)
Timor Leste is one of the countries in the world that uses the two Official Languages (Officially Bilingual), namely Portuguese and Tetum. Both the languages and used as a communication tool in the office, school or other places. While English used as working language and compulsory subject in school and university. In the schools, English is taught as second language. Students often have difficulty in understanding English texts. To facilitate better understanding of vocabulary and grammar, they are likely to translate into Tetum language or vice versa. However, in translation often encounter several errors. This study aims to determine what are problems faced by students when they translate text from English language to Tetum language. In addition to analyze kinds of errors that they write in text which they translate and analyze source of error. Method used for this research is descriptive qualitative method, while the samples used in twelve classes only taken one class to research using random sampling. To obtain data in this study, the writer uses text in Tetum with the title "Wainhira ita lokon etika" or "When did we lose ethics?" Which will be translated into English, the author also conducted observation studies that aims at determining problems arise in classroom when students are being translated the texts and interviews to some of the students to determine what problems they face when they translate text from Tetum to English. From the results of the study it is found that kinds of errors in translation are: competence error, error performance, fundamentally error consisting of local and global error and the author uses surface strategy taxonomy such as: omission, addition, misinformation and misordering. While the source of errors in the translation found four things, namely overgeneralization, ignorance of Rule Restrictions, incomplete application of rules restrictions and false concept hypothesized. Students have a lot of trouble for did translation. It can be seen from result of their translation. In general, the students felt overwhelm and difficult to put their ideas in a coherent way. Students did not know how to write correct English sentences. They translated word by word as the result translation has shifted from real meaning. Other problems, Students have problem in placement and the use verbs in their sentences From these results the writer concluded that there is a need for a teacher to gives translation exercises to students so that teachers can know weaknesses and shortcomings of the students through text they translated, for the necessity of the need for teachers to provide training on this to students, because by doing translation can add students vocabulary, train them to construct grammatical sentences correctly based on what they have learned in school.